A Simple Nonparametric Test for Independence - Bruce Mizrach (Rutgers University, Department of Economics, 1995)
A stationary stochastic process is defined to be locally independent if it eventually becomes independent of pastrealizations. I develop a simple nonparametric test for this condition. Size and power comparisons favor this statistic over the one proposed by Brock, Dechert and Scheinkman (1987) in samples under 250 observations.
Keywords: C14; 330; nonlinear dependence; U-statistics